2017
DOI: 10.1016/j.arth.2016.11.054
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Head Displacement and Disassembly Force With Increasing Assembly Load at the Head/Trunnion Junction of a Total Hip Arthroplasty Prosthesis

Abstract: An assembly force of 2 kN may be too low to overcome the frictional forces needed to engage the head and achieve maximum displacement on the trunnion and thus an assembly load of greater than 2.5 kN is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 20 publications
0
13
1
Order By: Relevance
“…During femoral head and trunnion assembly, care should be taken to make certain the trunnion is dry and void of any debris before assembly. While many manufacturers do not offer optimal assembly technique guides [43] it has been determined that an axially directed force of over 2.5kN should be utilized to optimize the modular connection between the head and trunnion of the stem [44]. When dealing with a revision scenario for a corroded trunnion, it has been shown that cleaning the trunnion and placing a new femoral head (CoCr or Ceramic) has no difference in stability of the head trunnion junction compared to pristine new tapers [45].…”
Section: Trunnion Corrosionmentioning
confidence: 99%
“…During femoral head and trunnion assembly, care should be taken to make certain the trunnion is dry and void of any debris before assembly. While many manufacturers do not offer optimal assembly technique guides [43] it has been determined that an axially directed force of over 2.5kN should be utilized to optimize the modular connection between the head and trunnion of the stem [44]. When dealing with a revision scenario for a corroded trunnion, it has been shown that cleaning the trunnion and placing a new femoral head (CoCr or Ceramic) has no difference in stability of the head trunnion junction compared to pristine new tapers [45].…”
Section: Trunnion Corrosionmentioning
confidence: 99%
“…When all other parameters are equal, MacLeod's model estimates a higher fixation force than Fessler's model by about a third ( Figure 2). However, when considering the technical aspects of the different experimental setups, nearly all fixation force values described in the literature correspond to the values estimated by Fessler's formula, ranging 40% to 55% of the impaction force [6,21,44,[47][48][49][50][51][52]. Surprisingly, the values measured by MacLeod et al do not correspond to those estimated by their own model [43].…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 70%
“…In both models, the fixation force correlates linearly with the force applied to impact the taper. The fixation force, therefore, has a major effect on the stability of the taper connection [6,[44][45][46][47][48][49][50][51][52]. Because the taper angle α is determined by the chosen prosthesis design (typically between 5 • 30 and 6 • [36]), this parameter has to be considered as fixed.…”
Section: Technical Aspects Of Taper Connections In Hip Arthroplastymentioning
confidence: 99%
“…However, these were only trials on a test rig, so it must be assumed that the absolute values in surgery are different due to soft tissue damping. Nevertheless, the study shows that the assembly forces can vary greatly between surgeons and that this in uences the strength of a Morse taper junction [14,15]. The aim of this study was to investigate the assembly forces of different surgeons under in situ conditions.…”
Section: Introductionmentioning
confidence: 99%